2006
DOI: 10.1159/000093380
|View full text |Cite
|
Sign up to set email alerts
|

Opinions on Cochlear Implant Use in Senior MED-EL Patients

Abstract: This study assessed the subjective benefits of cochlear implants in senior patients wearing a MED-EL device. Data was compared with previous studies to assess the influence of recent speech-coding strategies and behind-the-ear speech processors; users of the behind-the-ear device and the body-worn device were also compared. An adaptation of the Nucleus 22-channel survey was sent to 141 cochlear implant users. The survey assesses perception of the device, communication benefits, handling the device and quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The marvel of the vestibular system is its ability, more than other sensory systems, to readjust to changing conditions and environment. Disequilibrium was reported as a frequent minor post-CI complication [1,3,20,21] . However, postoperative vestibular problems in elderly CI recipients should be specially addressed since they may result in decreased quality of life associated with falling.…”
Section: Discussionmentioning
confidence: 99%
“…The marvel of the vestibular system is its ability, more than other sensory systems, to readjust to changing conditions and environment. Disequilibrium was reported as a frequent minor post-CI complication [1,3,20,21] . However, postoperative vestibular problems in elderly CI recipients should be specially addressed since they may result in decreased quality of life associated with falling.…”
Section: Discussionmentioning
confidence: 99%
“…Waltzman et al [33] had similar findings in their group of 20 patients aged 65-85 years implanted with Nucleus CIs. A more recent study by Anderson et al [43] surveyed 91 MED-EL CI recipients using a 30-item questionnaire based on the 26-item Cochlear Implant Questionnaire of Horn et al [31] . They then compared their group's results with older results of Horn et al [31] and Kelsall et al [32] and found significantly better outcomes in several areas for the newer technology including the ability to distinguish between a man's and a woman's voice, use of the telephone without a code, and overall increase in social activity since implantation.…”
Section: Cis and Qolmentioning
confidence: 99%
“…However, the majority of studies conclude that elderly patients exhibit improved hearing results after CI. [12][13][14] The purpose of this study was to review the audiological outcomes and the QOL in elderly patients who underwent CI in 3 institutions, as well as to compare these results to those achieved by younger adults under similar conditions.…”
Section: Introductionmentioning
confidence: 99%